Effect of foliar application of potassium on wheat tolerance to salt stress - Fiza Noor; Humera Nawaz; Ameer Khan; Muhammad Yousaf Shani; Muhammad Azmat; Syed Mohsin Abbas; Iqra Arshad; Robina Aziz; Muhammad Saleem; Francesco De Mastro; Muhammad Yasin Ashraf; Gennaro Brunetti; et al. (PLoS ONE, 2025)
Salinity stress severely hampers wheat productivity by impairing growth, photosynthesis, and metabolic balance. Potassium nutrition, however, can mitigate these effects by supporting physiological and biochemical stability. This study assessed the impact of foliar potassium application (0, 200 and 400 ppm) on two wheat cultivars, Galaxy-13 and Uqab-2000, exposed to normal (0 mM NaCl) and saline conditions (100 and 150 mM NaCl, respectively). Salinity significantly reduced root and shoot growth, biomass, chlorophyll content, photosynthetic rate, and stomatal conductance. Potassium supplementation, particularly at 400 ppm, alleviated these reductions, with Galaxy-13 showing a 32.01% increase in shoot length and a 45.11% increase in shoot dry weight compared to Uqab-2000. Biochemical analyses revealed that Galaxy-13 sustained higher nitrate and nitrite reductase activities (6.23 and 3.63 μmol NO 2 g -1 FW h -1 , respectively) and total soluble proteins (10.1 mg g -1 FW), whereas Uqab-2000 accumulated more soluble sugars and free amino acids under stress (9.8 and 19.8 mg g -1 FW, respectively). Oxidative stress indicators (malondialdehyde and hydrogen peroxide) rose under salinity, but potassium reduced their levels, with Galaxy-13 exhibiting stronger antioxidant regulation. Nutrient profiling further demonstrated that Galaxy-13 maintained higher N, P, and K contents and minimized Na uptake, unlike Uqab-2000, which showed severe ionic imbalance. Multivariate analyses (PCA, heatmap, and correlation) highlighted strong positive associations of potassium, especially K400, with biomass accumulation, photosynthetic efficiency, and nutrient homeostasis. The findings establish that Galaxy-13 possesses superior salinity tolerance and responds more favorably to potassium nutrition. This study provides novel evidence that cultivar-specific potassium management can enhance wheat resilience in saline environments, offering a practical strategy for sustaining yield under stress.